Bureaucratism as a phenomenon of rational bureaucracy: the reasons of appearance and the ways of overcoming - V. D. Bodnarchuk (Aspekti Publìčnogo Upravlìnnâ, 2016)
The essence and contents of the concepts «bureaucracy» and «bureaucratism» in domestic and foreign science are researched. Generalized definitions of these concepts from a position of public administration are proposed. It is proved that the bureaucracy is a necessary condition for the existence of public administration, without that it cannot perform its functions. As for the bureaucratism, it is negative and even destructive phenomenon, that destroys laws and social rules, limits public participation in making public and administrative decisions, slows reforms in the country. The reasons of the bureaucratism’s appearance in the system of public administration are analyzed, namely: the low professional and moral level of civil servants, the excessive politicization of public and administrative apparatus, the insufficient development of civil society institutions, including independent media, and the general low level of public consciousness and activity. It was demonstrated that the objective gap between the Max Weber’s bureaucracy ideal model and real public administration system is always a place for the signs of bureaucratism, such as formalism, individualism, automatism, that reduce the public administration effectiveness. Therefore the de-bureaucratization ways finding should not behave to full eradication of bureaucratism’s phenomenon that is a priori impossible, and to creating the conditions that makes it impossible the bureaucratism’s most threatening for the society forms - careerism, protectionism, bribery. The ways to bureaucratism’s overcoming, in particular through the institutionalization of civil society, the system auditing of public activities and the implementation of market processes in public administration, are suggested. The complex of these measures will contribute to rationalization and de-bureaucratization of public administration activity.